A Study of the Components of Revolutionary Education Underlying Islamic Civilization: a Research Based on the Content of the Statement of the Second Step of Islamic Revolution - Fatemeh Alipoor (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to explain the components of revolutionary education underlying Islamic civilization with an emphasis on the Statement of the Second Step. This research is qualitative and in terms of purpose is considered explorative. The research population and domain involve the Statement of the Second Step as well as speeches of the Supreme Leader about revolutionary education and Islamic civilization. The data of research was collected using document study and note taking. Besides, content analysis has been used for the identification of the themes. For extracting the subjects, criteria, and indicators for achieving the model of revolutionary education, the text of the Statement of the Second Step as well as the speeches of the Supreme Leader were reviewed. The data was analyzed using the method of content analysis. In this procedure, the following themes were derived: 159 basic contents, 25 organizing contents for spirituality and ethics, foundations and values of the revolution, cultural components of the revolution, raising political awareness, revolutionary achievements, self-esteem, insight, idealism, knowledge, research and technology, paying attention to the promising potential of the country, development, unity of the nation, constructive monitoring, responsibility, Islamic life style as well as pervasive contents including the main axes of the revolution, causes and requirements of revolutionary training, and its obstacles.